Pengaruh Situational Awareness dan Work Engagement Terhadap Turnover Intention dengan Organizational Commitment Sebagai Variabel Intervening Karyawan Rumah Sakit Annisa Cikarang - Aamdissofi, Adis; Rini, Tjipto; Silviana, Intan (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Annisa Hospital Human Resource Development data shows a tendency to increase employee turnover. From the 2022-2023 data, the percentage increase in turnover was 14.95%, rising to 16.64%. This turnover value is said to be quite high and has increased in percentage. This study aims to test the effect of situational awareness, work engagement on turnover intention with organizational commitment as an intervening variable for employees. The approach used is a quantitative approach. The sample used in this study were 169 permanent employees. Sampling was carried out by simple random sampling. Research data were obtained from filling out questionnaires and analyzed using the SEM PLS technique. The results of this study indicate that situational awareness, work engagement, organizational commitment each have a negative effect on turnover intention. Situational awareness and work engagement each have a positive effect on organizational commitment. Organizational commitment acts as an intervening factor for the influence given by situational awareness and work engagement on turnover intention. In order to reduce the high turnover intention, effective communication is needed, providing bonuses to employees according to their target achievements, providing enthusiasm and motivation to employees of Annisa Cikarang Hospital.